Differential Regulation of Neuropeptide Y in the Amygdala and Prefrontal Cortex during Recovery from Chronic Variable Stress - McGuire, Jennifer L.; Larke, Lauren; Sallee, Floyd; Herman, James; Sah, Renu (Frontiers in Behavioral Neuroscience, 2011)
Accumulating evidence from clinical studies and pre-clinical animal models supports a role for neuropeptide Y (NPY) in adaptive emotional response following stress. The long-term impact of stress, particularly chronic stress, on availability and function of resilience factors such as NPY may be critical to understanding the etiology of stress-related psychopathology. In these studies, we examined expression of NPY during recovery from a chronic variable stress (CVS) model of repetitive trauma in rats. Due to the importance of amygdala and prefrontal cortex in regulating emotional responses, we predicted chronic changes in NPY expression could contribute to persistent behavioral deficits seen in this model. Consistent with the hypothesis, ELISA for NPY peptide identified a significant reduction in NPY at the delayed (7 days) recovery timepoint. Interestingly, a significant increase in prefrontal NPY was observed at the same recovery timepoint.. The mRNA expression for NPY was not changed in the amygdala or PFC, although there was a modest but not statistically significant increase in NPY mRNA at the delayed recovery timepoint in the prefrontal cortex. The observed changes in NPY expression are consistent with maladaptive coping and enhanced emotionality, due to the nature of NPY signaling within these respective regions, and the nature of reciprocal connections between amygdala and prefrontal cortex.